Synthesis and crystal structure of a palladium(II) complex with the amino acid L-citrulline. Issue 4 (2nd September 2015) - Mascaliovas, Bruno Z.; Bergamini, Fernando R.G.; Cuin, Alexandre; Corbi, Pedro P.
Abstract : Synthesis and structural characterization of a novel palladium Pd(II) complex with the amino acid L-citrulline (Cit, C6 H13 N3 O3 ) are presented in this paper. Elemental analysis indicates a 1:2 metal/ligand molar composition for the complex, with the molecular formula PdC12 H24 N6 O6. The compound was also characterized by infrared (IR) spectroscopic measurements and the crystal structure has been solved by powder X-ray diffraction data with simulated annealing strategy in real space. The Pd(II) complex crystallizes in the triclinic system with space group P-1 and cell parameters a = 4.6493(4) Å, b = 5.222(4) Å, c = 18.040(2) Å, α = 77.41(6)°, β = 94.72(7), ° and γ = 101.45(7)°. The crystal structure confirms the presence of Pd(II) ions in a nearly square planar environment and the molecular formula with deprotonated citrulline as proposed by analytical and spectroscopic data.